Pharmacotherapeutic Properties of Telfairia occidentalis Hook F.: A Systematic Review - Aworunse, Oluwadurotimi Samuel; Bello, Oluwakemi Adetutu; Popoola, Jacob Olugbenro; Obembe, Olawole Odun (Pharmacognosy Reviews)
Globally, there has been a growing interest in medicinal plants by researchers. Telfairia occidentalis Hook F. (Fluted pumpkin) is cucurbitaceous vegetable grown in West Africa, particularly in Nigeria for its leaves and seeds. The curative properties of fluted pumpkin are popular in Nigerian folklore medicine, and several investigators have validated these therapeutic effects using animal models. The aim of this work therefore, was to review publicly available literature on the pharmacotherapeutic activities of T. occidentalis. Searches were performed on PubMed, Scopus, ScienceDirect, and Google Scholar for related studies, with search dates set between 1990 and 2018. A total of 499 articles were retrieved and analyzed, with 38 studies ultimately retained. Studies contained in this review were carried out in Nigeria, across different locations. 13 categories of pharmacological activities for fluted pumpkin were documented after analyzing full texts of the articles retained. T. occidentalis offers myriad of healing properties that can be explored by pharmaceutical industries. As the search for potent drugs from botanical sources continues, there is need for future investigations to isolate and characterize pharmacologically active agents that confer medicinal properties on fluted pumpkin, as well as elucidate the structures of these agents and pathways by which they exert their healing properties.
Keywords: Fluted pumpkin; medicinal plant; pharmacological; Telfairia occidentalis; therapeutic